2019
DOI: 10.22438/jeb/40/3(si)/sp-05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corn straw manure as dairy manure on productivity and profitability of wheat at huang-huai-hai plain

Abstract: The study aimed to assess the effect of corn straw as dairy manure on productivity and profitability of wheat and then set up fertilization scheme of wheat-corn cropping system. Fourteen treatments of N, P O and K O fertilizer was carried out in the field, where corn was 2 5 2 used as silage corn, and dairy manure was returned to customary field. Yield, wheat price, fertilizer cost and incidental expense were investigated. The relationship between the amount of fertilizer and wheat yield was studied. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The highest gross, net returns and B: C ratio were obtained by Joshi et al (2019) an application of higher rates of nutrients, i.e., with 125% RDF. Sui et al (2019) also reported significant economic benefits with manure in wheat.…”
Section: Resultsmentioning
confidence: 99%
“…The highest gross, net returns and B: C ratio were obtained by Joshi et al (2019) an application of higher rates of nutrients, i.e., with 125% RDF. Sui et al (2019) also reported significant economic benefits with manure in wheat.…”
Section: Resultsmentioning
confidence: 99%